2022
DOI: 10.1080/15440478.2022.2124217
|View full text |Cite
|
Sign up to set email alerts
|

The Water Absorption and Thermal Properties of Green Pterocarpus Angolensis ( Mukwa )-Polylactide Composites

Abstract: The water absorption, chemical resistance and biological properties are contributing factors to the overall performance of bio-composites, especially for outdoor applications. The functional properties of bio-composites are dependent on the interfacial bonding mechanism, which is controlled by the surface modification and processing parameters of natural fibers. Therefore, this study aims to investigate the potential of enhancing the mukwa/polylactide (mukwa/PLA) interface through an economic and ecological su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…It was observed that, for 4P5J – 1, the hybridization of pineapple increased the moisture absorption significantly (an increase of 22.5% compared to JFRP) after 21 days. This could be attributed to a combination of factors, including the presence of more hydroxyl groups in the jute-cotton fibre ply (which can form hydrogen bonds with water molecules, leading to water retention [ 85 ]), which was on the outside of the composite, and poor interfacial adhesion between the alternating jute/PALF plies and the matrix, facilitating enhanced moisture absorption through capillary effect and microcracking [ 86 ]. The presence of voids observed in the SEM micrograph of 4P5J-1 may also contribute to water retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that, for 4P5J – 1, the hybridization of pineapple increased the moisture absorption significantly (an increase of 22.5% compared to JFRP) after 21 days. This could be attributed to a combination of factors, including the presence of more hydroxyl groups in the jute-cotton fibre ply (which can form hydrogen bonds with water molecules, leading to water retention [ 85 ]), which was on the outside of the composite, and poor interfacial adhesion between the alternating jute/PALF plies and the matrix, facilitating enhanced moisture absorption through capillary effect and microcracking [ 86 ]. The presence of voids observed in the SEM micrograph of 4P5J-1 may also contribute to water retention.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for all the other composites, hybridization effectively reduced moisture absorption to approximately 16.70%, 14.84%, and 29.50% for 4P5J – 2, 4P5J – 3, and 4P5J – 4, respectively, when compared to the moisture absorption of 12.44 wt% JFRP after 21 days. The significant reduction in moisture absorption may be attributed to a lower presence of hydroxyl groups on the composite surface [ 85 ] as well as improved surface adhesion when stacking the same type of plies together.…”
Section: Resultsmentioning
confidence: 99%
“…When the percentage of jute fiber in the material rises to 10% and then 15%, the strength drop becomes more obvious. Hydrolysis, caused by absorbed water, weakened the fibers and reduced their mechanical characteristics, lowering the composite's strength [37][38].…”
Section: Effect Of Water Absorptionmentioning
confidence: 99%